The didactic laboratory of the pedagogical museum of Castelló. Development of a proposal for action through PAR processes - Lapiedra-Ortega, Mark; Traver Martí, Juan Andrés (European Public & Social Innovation Review, 2025)
Introduction: The Pedagogical Museum of Castelló, located at Jaume I University, is dedicated to preserving the educational heritage of the region by restoring and exhibiting objects linked to the history of education. It also serves as a center for training, research, and pedagogical innovation. In this context, this study proposes the creation of a didactic laboratory that will give a second life to the materials housed in the museum. Methodology: Participatory Action Research methodology was used, allowing for the collection of knowledge from various stakeholders to design an action plan based on their experiences and needs. Eleven people participated, including active and retired teachers, students of Early Childhood Education and the Master's program in Psychopedagogy, as well as university administrative and service staff. Results: The findings reflect a shared vision of the laboratory as a space for exploration and active research, transcending mere exhibition to become a living tool for knowledge construction. Discussion: Michel Foucault's concept of "archive" served as a theoretical basis for understanding how educational heritage can generate new forms of knowledge. Conclusions: The project promotes a reinterpretation of the museum's historical materials, proposing a laboratory where educational memory is transformed into pedagogical innovation.